2019
DOI: 10.15611/aoe.2019.1.06
|View full text |Cite
|
Sign up to set email alerts
|

How does economic policy uncertainty affect prices of housing? Evidence from Germany

Abstract: We test the interaction between housing prices and economic policy uncertainty with controlling for the effect of the interest rate in Germany. A bootstrap rolling-window Granger causality test method is utilized for the purpose of detecting their dynamic relationship, since we find significant structural changes across the full-sample of the time series which should be taken into account to avoid estimation errors, and more importantly to get a more instructive conclusion. We find that even in Germany, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A visual examination of Figure 7 makes the focus on housing market research apparent (Andre et al ., 2017; Marfatia et al ., 2022; Miles, 2009). Despite the plethora of uncertainty indicators available, most studies have adopted the EPU, which tracks the prevalence of keywords such as uncertainty and economy in each country's top newspapers (Fu et al ., 2021; Gholipour et al ., 2022; Ongan and Gocer, 2017; Su et al ., 2019). GFC and COVID-19 are also commonly occurring terms due to the reported adverse impacts of these disruptions on a global scale (Al-Thaqeb et al ., 2022; Cheung et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A visual examination of Figure 7 makes the focus on housing market research apparent (Andre et al ., 2017; Marfatia et al ., 2022; Miles, 2009). Despite the plethora of uncertainty indicators available, most studies have adopted the EPU, which tracks the prevalence of keywords such as uncertainty and economy in each country's top newspapers (Fu et al ., 2021; Gholipour et al ., 2022; Ongan and Gocer, 2017; Su et al ., 2019). GFC and COVID-19 are also commonly occurring terms due to the reported adverse impacts of these disruptions on a global scale (Al-Thaqeb et al ., 2022; Cheung et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The result shows a positive and significant relationship between the two variables in the short run. Su et al (2019) used the bootstrap rolling-window Granger causality test and showed that economic policy uncertainty affects house prices positively or negatively. Moreover, the house price volatility increases the economic policy uncertainty, whereas economic policy uncertainty reduces the house price volatility.…”
Section: Empirical Studiesmentioning
confidence: 99%